Unilateral, Isolated, Paediatric Lightning-Induced Cataract: A Case Report - G. J. Rogers; R. Grotte (Case Reports in Ophthalmological Medicine)
A six-year-old girl presented with gradual loss of vision in the left eye a year after sustaining a lightning strike while in her home. Examination revealed healed burns to her cheek, left arm, and right leg and a dense left cataract. There was no evidence of other ocular sequelae, and her right eye was normal. Cataract surgery and lens implantation were performed on the left eye with good results. Isolated, unilateral, paediatric cataract due to lightning is discussed.